Training For Trainers In Critical Digital Literacy Skills For Teachers’ Activist - Anggraini, Clara Novita; Kusumaningrum, Yucha Febria (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Internet users in Indonesia have increased in the last three years. In 2021-2022, 77.02% (more than 210 million people) of Indonesia's population are penetrated by the Internet. Unfortunately, Indonesia's digital literacy is in the moderate stage, with a score of 3.49. The level of digital literacy in Indonesia is not well distributed. People in rural areas have a lower digital literacy index than those in urban areas. Based on this situation, it can potentially produce digital literacy training. Teachers in rural areas play an essential role. They may become role models in forming a critical mindset for their students in digital media. To hold this training, we collaborate with Sekolah Guru Indonesia Dompet Dhuafa. The participants have conducted digital literacy training for teachers in their domicile before this training. They also passed some selections before joining this training. We named this event Training for Trainers Level 2. This training is part of Digital Literacy Education Program for Activists Sekolah Guru Indonesia collaborate with Dompet Dhuafa. The participants consisted of 20 teachers who represented various regions in Indonesia. The training was held online and consisted of two parts of meetings. The output of this community development program is publication in the mass media, a book of digital literacy awareness written by participants, and a Podcast's Intellectual Property Rights made by the best participants.